Regularities of Fluoropolymer Coating Growth on Pretreated Surfaces from Active Gas Phase; Materials Science Forum; Vol. 970 : Modern Problems in Materials Processing, Manufacturing, Testing and Quality Assurance II - Rogachev A. A. Alexander; Luchnikov P. A. Petr; Sarkisov O. A. Oleg; Rogachev A. V. Alexander; Plotnikova I. V. Inna Vasilievna (2019, 2019)
Title screen